Large-Scale Multiobject Emulation Platform for Noncooperative Target Missions in Space - Hao Chi; Guolei Wang; Ken Chen; Jiwen Zhang (International Journal of Aerospace Engineering)
On-ground emulation is crucial to cutting-edge space technology involving the rendezvous and maintenance of noncooperative objects. However, existing systems are restricted to two objects and have a limited range of motion, and they cannot emulate some real space missions. The introduction of mobile robots is a potential solution, but on the one hand, their relatively low precision may ruin the emulation; on the other hand, how to take full advantage of mobile robots’ larger range of motion in on-ground emulation is still to be solved. This paper presents a novel emulation platform for noncooperative object missions in space that can complete high-precision kinetic emulations of large-scale and multiobject motion. We use different kinds of mobile robots in our system and overcome the poor kinetic accuracy of mobile platforms. First, the composition and kinetics of the whole system are characterized. We simplify the hyper-redundant system and propose a trajectory mapping method based on the workspace of mobile manipulators. Then, a dynamic programming method is proposed to plan the joint trajectories of mobile manipulators. We propose a feasibility function based on manipulability and the singularity avoidance coefficient, which ensures that the mobile base moves smoothly and that high-precision manipulators have enough space to compensate for the movement errors of mobile bases. Finally, experimental results verify the feasibility and effectiveness of the system and the planning methods.